The Public Interest and Public Broadcasting: Looking at Communications As a Whole - Nicholas Johnson (Washington University Law Quarterly, 1967)
In this Article, Federal Communications Commissioner Nicholas Johnson indicates the public's interest in broadcasting and the importance of the President's “Message on Communications Policy.” He argues that it is critical at this stage of development to look at communications as a whole, not isolated segments. In the appendix, we reproduce the recently passed Public Broadcasting Act which creates a publicly financed corporation to produce television programs.
Keywords: Communications; Public interest